The impact of MgO nanoparticle interface in ultra-insulating polyethylene nanocomposites for high voltage DC cables. Issue 22 (27th April 2016) - Pallon, L. K. H.; Hoang, A. T.; Pourrahimi, A. M.; Hedenqvist, M. S.; Nilsson, F.; Gubanski, S.; Gedde, U. W.; Olsson, R. T.
Abstract : Ultra-insulating polyethylene nanocomposites were achieved by appropriate MgO nanoparticle surface modification, resulting in unprecedented dispersion and 2 orders of magnitude lower conductivity. Abstract : Low density polyethylene (LDPE) nanocomposites with a reduced conductivity of two orders of magnitude are reported as a novel insulation material for high voltage distribution of renewable energy. The key to the high insulation capacity was to provide 70 nm hexagonal MgO nanoparticles with relatively long, preferably 18 units long, hydrocarbon functional silsesquioxane coatings. This rendered the surface of the particles completely hydrophobic and also served as a protective layer against adsorption of polar low molecular weight atmospheric substances (H2 O and CO2 ). The elimination of trace amounts of water, in combination with the provided carbon functionality, dramatically improved the dispersion of MgO nanoparticles. The lowest volume conductivity was ca. 7 × 10 −16 S m −1 for 3 wt% surface coated nanoparticles. Extensive electron microscopy characterization was further used to relate the measured volume conductivity, acquired under conditions that resemble 800 kV high voltage direct current (HVDC) cables, to the distribution of the nanoparticles in the polymer matrix. The results show that an appropriate surface-modification approach yielded uniformly dispersed MgO nanoparticles up to contents as high as 9 wt%, with maintained 10–100 times reduced volume conductivity. Simulations of the MgO nanoparticles distribution revealed that the required interaction radius of the MgO-phase was 775 nm, setting a lower limit of particle amount to effectively work as electrical insulation promoters. The reduced volume conductivity values and scalable processing chemistry reported allow for the production of the next generation insulation material for HVDC cables.